Johann Sebastian Bach’s Prelude Score Study-BWV 998 Works - Hananto, Paulus Dwi; Soesila, Poedji (Universitas Negeri Surabaya, 2024)
Researchers compared the Prelude BWV 998 by Johann Sebastian Bach, the transcriptions of Andres Segovia and Frederick Zigante. The background is to increase the understanding of the general public, especially players and music students with major guitar instruments, about how to interpret Baroque music correctly, because this composition was originally not for the guitar instrument but the lute. The method that researchers use is a qualitative method because it does not use numbers in this research process. The object of this research is Prelude is the opening composition of Prelude-Fuga-Allegro BWV 998 which was transcribed into guitar score by Andres Segovia and Frederick Zigante. Data collection was carried out by means of documentation and observation. The results of this research show that there are several differences in transcription including; playing techniques, such as the use of legato, finger positions, especially the left hand, interpretation signs, and different strings for the same note. This difference in transcription will greatly influence the guitar player's playing because it is adapted to the transcription style, thereby changing the character of the original composition.